2002
DOI: 10.1161/01.hyp.0000028978.99648.d0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Office and Ambulatory Blood Pressure Measurements in Pregnancy

Abstract: Abstract-With the objective to assess the prognostic value of office values as compared with ambulatory monitoring in pregnancy, we analyzed 2430 blood pressure series systematically sampled from 403 untreated pregnant women for 48 consecutive hours every 4 weeks from the first visit to the hospital until delivery. Women were divided into 5 groups: "detected" gestational hypertension, women with office blood pressures Ͼ140/90 mm Hg after 20 weeks of gestation and hyperbaric index (area of blood pressure excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 33 publications
2
45
2
Order By: Relevance
“…11 Against the common approach of relying on the 24-hour mean of ABPM, the combined approach of establishing tolerance intervals for the circadian variability of BP as a function of gestational age 25 and then computing the hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile with those intervals, has been shown to provide high sensitivity and specificity for the early detection of pregnant women who will have subsequent development of gestational hypertension or preeclampsia 12 as well as a proper approach for the prediction of the outcome of pregnancy. 26 Results from this trial on the impact of the duration and frequency of BP sampling on the reproducibility of mean values indicate that parameters calculated from the ABPM profile are much more dependent on duration of sampling than on sampling rate. Thus, Figures 1 and 2 indicate that the 24-hour mean of BP can be better estimated by expanding the length of the monitoring span to 48 hours, even by markedly reducing the frequency of sampling up to only 1 value every 3 hours.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…11 Against the common approach of relying on the 24-hour mean of ABPM, the combined approach of establishing tolerance intervals for the circadian variability of BP as a function of gestational age 25 and then computing the hyperbaric index (area of BP excess above the upper limit of the tolerance interval) by comparison of any patient's BP profile with those intervals, has been shown to provide high sensitivity and specificity for the early detection of pregnant women who will have subsequent development of gestational hypertension or preeclampsia 12 as well as a proper approach for the prediction of the outcome of pregnancy. 26 Results from this trial on the impact of the duration and frequency of BP sampling on the reproducibility of mean values indicate that parameters calculated from the ABPM profile are much more dependent on duration of sampling than on sampling rate. Thus, Figures 1 and 2 indicate that the 24-hour mean of BP can be better estimated by expanding the length of the monitoring span to 48 hours, even by markedly reducing the frequency of sampling up to only 1 value every 3 hours.…”
Section: Discussionmentioning
confidence: 81%
“…Gestational hypertension was defined as conventional BP values Ͼ140 or 90 mm Hg for systolic (SBP) or diastolic BP (DBP), respectively, after the 20th week of gestation, and/or a hyperbaric index (area of BP excess above the upper limit of a time-varying tolerance interval 25,26 ) consistently above the threshold for diagnosis of hypertension in pregnancy 12 after the 20th week of gestation for further corroboration. Preeclampsia was defined as gestational hypertension and proteinuria Ͼ300 mg in 24 hours of urine collection.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that a relatively large proportion of pregnant women may have masked gestational hypertension, undetected by office BP measurements, but revealed by specific BP index or circadian patterns computed with ambulatory BP monitoring. [31][32][33] Notably, pregnant women at increased risk of hypertension disorders tend to have higher night-time ambulatory BP than women without development of hypertension complications during pregnancy. 33 At the same time, night-time ambulatory BP is an independent predictor of LA size in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hermida, et al [30] have shown that, in pregnancy, the hyperbaric index (area of BP excess above the upper limit of a time-specified tolerance interval) derived from ABPM was superior to office measurements for predicting the outcome of pregnancy.…”
Section: Ecgmentioning
confidence: 99%